CONCEPTUL DE MODULARE A GAZDEI IN TERAPIA PARODONTALA - Sorina Mihaela Solomon; Liliana Păsărin; Irina Georgeta Sufaru; Silvia Mârţu (Romanian Dental Association for Education, 2017)
Host modulation therapy, although not a novelty in medicine, has recently been proposed as an adjunct to conventional treatment of periodontal disease. This innovative therapeutic approach has its origin in the latest data from fundamental research on the etiopathogeny of periodontal disease. Understanding the mechanisms of the disease as well as the ways in which different substances can intervene in the sense of both alleviating signs of disease or stimulating the host's protective mechanisms or increasing the effectiveness of conventional therapies has nowadays considered adjunctive therapy in Periodontal disease, the methods that are grouped into the concept of host modulation therapy.